FABRICATION & EXPERIMENTAL ANALYSIS OF HYBRID COMPOSITE MATERIAL (CARBON & E-GLASS) - RAJASEKHAR VANGALA; K.RAJU; RAVINDRA GANDHI M. (International Journal of Innovations in Engineering Research and Technology, 2021)
Composite materials are considered to be designer materials because of their ease in tailor ability of properties, high specific strengths, high specific modulus, low densities, etc .based on the application. Presently they are playing a vital role in aerospace, defence, transport, sport applications, worldwide researchers are keenly interested in finding out their behavior in real life exposed to various environmental conditions, variety of loads etc. The key interest in the research is due to the variable properties of the same material, same compositions with respect to the manufacturing process undergone.This paper deals the fabrication and experimentation deals with the know how the behavior and mechanical properties of E-glass epoxy composite and a hybrid composite made of E-glass and carbon fabric reinforcements and compared with the conventional materials.